Solid-state secondary battery positive electrode, solid-state secondary battery positive electrode preparation method and solid-state secondary battery
By adopting a multi-layer structure of solid secondary battery positive electrode, using low-temperature dry slurry and hot pressing to make a film, combined with the design of micron- and millimeter-level pores, the problem of high curvature of the ion transmission path in the solid-state battery positive electrode is solved, and the effect of improving rate performance and cycling stability is achieved.
Patent Information
- Application Number
- CN202411540121.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-03-18
AI Technical Summary
In the positive electrode structure design of solid-state batteries, the ion transmission path has high curvature, which limits the power density and is difficult to meet the needs of fast charging of electric vehicles.
The positive electrode of the solid secondary battery with a multi-layer structure includes the first, second and third layers. Each layer consists of small positive electrode particles, solid electrolyte particles, conductive agents and binders, and is prepared by low-temperature dry slurry and hot pressing to make a film. Combined with the design of micron- and millimeter-level pores, the solid electrolyte is filled to construct a channel for rapid lithium ions transmission.
The bending of the lithium ion transmission path is reduced, the rate performance and cycling stability are improved, and the energy density and extreme surface density of the battery are enhanced.
Smart Images

Figure CN119650577A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of solid-state secondary batteries, and in particular to a positive electrode of a solid-state secondary battery, a method for preparing a positive electrode of a solid-state secondary battery, and a solid-state secondary battery. Background Art
[0002] In recent years, solid-state batteries have attracted widespread attention from the industry as a highly safe electrochemical energy storage device. However, solid-state batteries still face many challenges, which makes it difficult for them to outperform existing lithium-ion batteries based on liquid electrolytes. One of the main challenges is the design of the positive electrode structure. The high tortuosity of the ion transmission path of the solid-state positive electrode limits the power density. As the fast charging requirements of electric vehicles become higher and higher, the above problems in solid-state positive electrodes need to be overcome to ensure that they meet the prerequisites for practical application. Summary of the invention
[0003] In response to the above technical problems, the purpose of the present application is to provide a solid-state secondary battery positive electrode, a method for preparing a solid-state secondary battery positive electrode and a solid-state secondary battery, aiming to reduce the curvature of the lithium ion transmission path while improving the rate performance.
[0004] In a first aspect, an embodiment of the present application provides a solid-state secondary battery positive electrode, comprising:
[0005] Positive electrode current collector;
[0006] A first layer located on the positive electrode current collector; the first layer comprises small positive electrode particles, small solid electrolyte particles, a conductive agent and a binder;
[0007] A second layer located on the first layer; the second layer further comprises positive electrode particles, solid electrolyte particles, a conductive agent and a binder;
[0008] a third layer located on the second layer; the third layer comprises small positive electrode particles, large solid electrolyte particles, a conductive agent and a binder; wherein the particle size of the small positive electrode particles is smaller than the particle size of the large positive electrode particles, and the particle size of the small solid electrolyte particles is smaller than the particle size of the large solid electrolyte particles;
[0009] Micrometer-sized pores distributed in the first layer, the second layer and the third layer; the micrometer-sized pores are filled with small solid electrolyte particles, a conductive agent and a binder;
[0010] Millimeter-scale holes penetrate the first layer, the second layer and the third layer, and are filled with small solid electrolyte particles, a conductive agent and a binder.
[0011] In a second aspect, an embodiment of the present application provides a method for preparing a positive electrode of a solid-state secondary battery, the method being used to prepare the above-mentioned positive electrode of a solid-state secondary battery, the method comprising:
[0012] The positive electrode small particles, solid electrolyte small particles, conductive agent, binder and dry ice particles are configured into a low-temperature dry slurry, which is coated on the positive electrode current collector and hot pressed into a film to form a first layer;
[0013] The cathode large particles, solid electrolyte small particles, conductive agent, binder and dry ice particles are configured into a low-temperature dry slurry, which is coated on the first layer and hot pressed into a film to form a second layer;
[0014] The small positive electrode particles, the large solid electrolyte particles, the conductive agent, the binder and the dry ice particles are configured into a low-temperature dry slurry, which is coated on the second layer and hot pressed into a film to form a third layer;
[0015] The formed three-layer electrode is then punched;
[0016] Small solid electrolyte particles, a conductive agent and a binder are prepared into a slurry, applied to the punched areas, and dried.
[0017] Furthermore, the step of configuring the positive electrode small particles, solid electrolyte small particles, conductive agent, binder and dry ice particles into a low-temperature dry slurry comprises:
[0018] The positive electrode small particles, solid electrolyte small particles, conductive agent, and binder are configured into a low-temperature dry slurry in a mass ratio of 60-85:14-30:0.5-5:0.5-5, and dry ice accounts for 0.5% to 5% of the total mass of the four substances of the positive electrode small particles, solid electrolyte small particles, conductive agent and binder in the first layer.
[0019] Furthermore, the step of configuring the large positive electrode particles, small solid electrolyte particles, conductive agent, binder and dry ice particles into a low-temperature dry slurry comprises:
[0020] The positive electrode huge particles, solid electrolyte small particles, conductive agent, and binder are prepared into a low-temperature dry slurry in a mass ratio of 70-97:2-20:0.5-5:0.5-5, and dry ice accounts for 0.5%-5% of the total mass of the four substances in the second layer, namely, the positive electrode huge particles, solid electrolyte small particles, conductive agent, and binder.
[0021] Furthermore, the step of configuring the positive electrode small particles, the solid electrolyte large particles, the conductive agent, the binder and the dry ice particles into a low-temperature dry slurry comprises:
[0022] The small positive electrode particles, large solid electrolyte particles, conductive agent, and binder are configured into a low-temperature dry slurry in a mass ratio of 45-79:20-45:0.5-5:0.5-5, and dry ice accounts for 0.5% to 5% of the total mass of the four substances in the third layer, namely, the small positive electrode particles, large solid electrolyte particles, conductive agent, and binder.
[0023] Furthermore, the step of configuring the solid electrolyte small particles, the conductive agent and the binder into a slurry comprises:
[0024] The solid electrolyte small particles, the conductive agent and the binder are prepared into a slurry in a mass ratio of 90-99:0.5-5:0.5-5.
[0025] Furthermore, the diameter of the hole formed by punching is 1 mm to 10 mm.
[0026] Furthermore, the diameter of the pores formed by the dry ice particles being vaporized under hot pressure is 0.1 micrometer to 10 micrometers.
[0027] In a third aspect, an embodiment of the present application provides a solid-state secondary battery, wherein the solid-state secondary battery includes the solid-state secondary battery positive electrode described above.
[0028] In an embodiment of the present application, the first layer includes small positive electrode particles, small solid electrolyte particles, a conductive agent and a binder. The first layer provides fast lithium ion and electron transmission, and reduces ohmic impedance and lithium ion transfer impedance. The second layer includes large positive electrode particles, small solid electrolyte particles, a conductive agent and a binder. The second layer provides fast lithium ion transport and high load and high pressure, and improves the surface density and energy density of the pole piece. The third layer includes small positive electrode particles, large solid electrolyte particles, a conductive agent and a binder. The third layer provides fast lithium ion transmission and electronic insulation, avoids the occurrence of interfacial side reactions, improves interfacial stability, and improves circulation. The micron-sized pores distributed in the first layer, the second layer and the third layer can increase the porosity and reduce the tortuosity. The solid electrolyte is filled in the micron-sized pores and the millimeter-sized pores to construct a channel for rapid lithium ion transmission, reduce the lithium ion transfer impedance, and improve the rate performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] In order to more clearly illustrate the technical solution of the present application, the drawings required for use in the implementation manner will be briefly introduced below. Obviously, the drawings described below are only some implementation manners of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0030] Figure 1 It is a schematic diagram of a process for preparing a positive electrode of a solid-state secondary battery provided in an embodiment of the present application;
[0031] Figure 2 It is a schematic diagram of coating three layers of slurry on the positive electrode current collector provided in an embodiment of the present application;
[0032] Figure 3 It is a schematic diagram of coating three layers of slurry on the positive electrode current collector and drilling holes provided in an embodiment of the present application;
[0033] Figure 4 It is a schematic diagram of coating three layers of slurry on the positive electrode current collector, drilling holes, and coating the slurry on the drilled holes, according to an embodiment of the present application. DETAILED DESCRIPTION
[0034] In order to make the purpose, technical solution and advantages of the present application more clearly understood, the present application is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.
[0035] It will be understood by those skilled in the art that, unless expressly stated, the singular forms "a", "an", "above", and "the" used herein may also include plural forms. It should be further understood that the term "comprising" used in the specification of the present application refers to the presence of features, integers, steps, operations, elements, modules, and / or components, but does not exclude the presence or addition of one or more other features, integers, steps, operations, elements, modules, components, and / or groups thereof. It should be understood that when we refer to an element as being "connected" or "coupled" to another element, it may be directly connected or coupled to the other element, or there may be an intermediate element. In addition, the "connection" or "coupling" used herein may include wireless connection or wireless coupling. The term "and / or" used herein includes all or any module and all combinations of one or more associated listed items.
[0036] It will be understood by those skilled in the art that, unless otherwise defined, all terms (including technical and scientific terms) used herein have the same meaning as those generally understood by those skilled in the art to which this application belongs. It should also be understood that terms such as those defined in general dictionaries should be understood to have meanings consistent with those in the context of the prior art, and will not be interpreted with idealized or overly formal meanings unless specifically defined as here.
[0037] The present application embodiment provides a solid-state secondary battery positive electrode, such as Figure 4 In the figure, the larger gray particles are large solid electrolyte particles, the smaller gray particles are small solid electrolyte particles, the larger black particles are large positive electrode particles, and the smaller black particles are small positive electrode particles. The positive electrode of the solid-state secondary battery includes:
[0038] Positive electrode current collector 1;
[0039] A first layer 2 located on the positive electrode current collector 1; the first layer 2 comprises small positive electrode particles, small solid electrolyte particles, a conductive agent and a binder;
[0040] A second layer 3 is located on the first layer 2; the second layer 3 also includes large positive particles, small solid electrolyte particles, a conductive agent and a binder;
[0041] A third layer 4 located on the second layer 3; the third layer 4 comprises small positive electrode particles, large solid electrolyte particles, a conductive agent and a binder;
[0042] Micrometer-sized pores distributed in the first layer 2, the second layer 3 and the third layer 4; the micrometer-sized pores are filled with small solid electrolyte particles, a conductive agent and a binder;
[0043] The millimeter-scale holes 5 penetrate the first layer 2, the second layer 3 and the third layer 4, and are filled with small solid electrolyte particles, a conductive agent and a binder.
[0044] In an embodiment of the present application, the first layer 2 includes small positive electrode particles, small solid electrolyte particles, a conductive agent and a binder. The first layer 2 provides fast lithium ion and electron transmission, reducing ohmic impedance and lithium ion transfer impedance. The second layer 3 includes large positive electrode particles, small solid electrolyte particles, a conductive agent and a binder. The second layer 3 provides fast lithium ion transport and high load and high pressure, and improves the surface density and energy density of the pole piece. The third layer 4 includes small positive electrode particles, large solid electrolyte particles, a conductive agent and a binder. The third layer 4 provides fast lithium ion transmission and electronic insulation, avoids the occurrence of interface side reactions, improves interface stability, and improves circulation. The micron-sized pores distributed in the first layer 2, the second layer 3 and the third layer 4 can increase the porosity and reduce the tortuosity. The solid electrolyte is filled in the micron-sized pores and the millimeter-sized pores 5 to construct a channel for rapid lithium ion transmission, reduce the lithium ion transfer impedance, and improve the rate performance.
[0045] It should be noted that, in the above, the positive electrode current collector 1 can be aluminum foil, carbon-coated aluminum foil or stainless steel foil. The small positive particles and the large positive particles are both positive electrode active materials. The small size of the small positive particles here is relative to the large size of the large positive particles, that is, the particle size of the small positive particles is smaller than that of the large positive particles. Similarly, the particle size of the small solid electrolyte particles is smaller than that of the large solid electrolyte particles. The particle size range of the small positive particles is 0.01umˉ10um, and the particle size range of the large positive particles is 10umˉ100um; the particle size range of the small solid electrolyte particles is 0.01umˉ15um, and the particle size range of the large solid electrolyte particles is 15umˉ500um, um is micrometer. The positive electrode material can be a positive electrode ternary NCM, lithium iron phosphate LFP, lithium manganese-rich LMR, lithium cobalt oxide LCO or lithium manganese iron phosphate LMFP, etc. The solid electrolyte can be: sulfide electrolyte: lithium phosphorus sulfur LPS, lithium phosphorus sulfur chlorine LPSCl, lithium germanium phosphorus sulfur LGPS, etc.; oxide solid electrolyte: lithium aluminum titanium phosphate LATP, lithium lanthanum zirconium oxide LLZO, lithium lanthanum titanium oxide LLTO, etc.; polymer solid electrolyte: polyethylene oxide PEO, polyvinyl carbonate PVC, polydioxolane PDOL, polysiloxane PS, polyethylene glycol PEG, etc. The conductive agent mentioned above can be carbon black SP, Ketjen black ECP, carbon nanotube CNT, graphene or vapor-grown carbon fiber reinforcement VGCF. The binder mentioned above can be polytetrafluoroethylene PTFE, polyvinylidene fluoride PVDF, P-type polyaniline PAN, polymethyl methacrylate PMMA or hydrogenated nitrile rubber HNBR, etc.
[0046] like Figure 1-4 As shown, the present application embodiment also provides a method for preparing a positive electrode of a solid-state secondary battery, the method is used to prepare the above-mentioned positive electrode of the solid-state secondary battery, the method comprising:
[0047] S1, preparing a low-temperature dry slurry of positive electrode small particles, solid electrolyte small particles, conductive agent, binder and dry ice particles, coating the slurry on the positive electrode current collector 1 and hot pressing the slurry to form a film, thereby forming a first layer 2;
[0048] S2, preparing a low-temperature dry slurry of positive electrode large particles, solid electrolyte small particles, conductive agent, binder and dry ice particles, coating the slurry on the first layer 2 and hot pressing the slurry to form a film, thereby forming a second layer 3;
[0049] S3, preparing a low-temperature dry slurry of positive electrode small particles, solid electrolyte large particles, conductive agent, binder and dry ice particles, coating the slurry on the second layer 3 and hot pressing the slurry to form a film, thereby forming a third layer 4;
[0050] S4, punching holes in the three-layer electrode sheet;
[0051] S5. Prepare a slurry of small solid electrolyte particles, conductive agent and binder, apply it to the punched holes, and dry it.
[0052] In step S1, positive electrode small particles, solid electrolyte small particles, conductive agent, binder and dry ice particles are configured into a low-temperature dry slurry in a certain proportion, and coated on any surface of the positive electrode current collector 1 for hot pressing to form a film, forming a first layer 2. The first layer 2 provides fast lithium ion and electron transmission, reduces ohmic impedance and lithium ion transfer impedance; during the hot pressing process of film formation, dry ice vaporizes and leaves the electrode, leaving holes at the original position, thereby increasing porosity and reducing tortuosity. The positive electrode current collector 1 can be aluminum foil, carbon-coated aluminum foil or stainless steel foil.
[0053] In step S2, large positive electrode particles, small solid electrolyte particles, conductive agent, binder and dry ice particles are configured into a low-temperature dry slurry in a certain proportion, coated on the first layer 2 and hot pressed into a film to form a second layer 3; the second layer 3 provides fast lithium ion transport and high load and high pressure, thereby improving the electrode surface density and energy density; during the hot pressing process of film formation, the dry ice vaporizes and leaves the electrode, leaving holes at the original position, thereby increasing the porosity and reducing the tortuosity.
[0054] In step S3, small positive electrode particles, large solid electrolyte particles, conductive agent, binder and dry ice particles are configured into a low-temperature dry slurry in a certain proportion, coated on the second layer 3 and hot pressed into a film to form a third layer 4. The third layer 4 provides fast lithium ion transmission and electronic insulation, avoids the occurrence of interface side reactions, improves interface stability, and enhances circulation. During the hot pressing process of film formation, the dry ice vaporizes and leaves the electrode, leaving holes at the original position, thereby increasing the porosity and reducing the tortuosity.
[0055] As described above, the dry ice particles are evenly distributed during the low-temperature dry pulping process, so the micrometer-sized pores 6 formed by the dry ice particles are evenly dispersed in the electrode.
[0056] In step S4, the three-layer electrode sheet is punched again until the positive electrode current collector, that is, the positive electrode current collector is not punched here. The punching method can be punching, drilling, photolithography or laser.
[0057] In step S5, small solid electrolyte particles, conductive agent and binder are configured into slurry in a certain proportion, applied to the punched holes, and dried. The solid electrolyte is filled in the micrometer-scale holes 6 left by the gasification of dry ice particles and the millimeter-scale holes 5 left by the punching, so as to construct a channel for rapid transmission of lithium ions, reduce the lithium ion transfer impedance, and improve the rate performance.
[0058] It should be noted that, in the above, the small positive electrode particles and the large positive electrode particles are both positive electrode active materials. The small size of the small positive electrode particles here is relative to the large size of the large positive electrode particles, that is, the size of the small positive electrode particles is smaller than the size of the large positive electrode particles. Similarly, the size of the small solid electrolyte particles is smaller than the size of the large solid electrolyte particles. The particle size range of the small positive electrode particles is 0.01umˉ10um, and the particle size range of the large positive electrode particles is 10umˉ100um; the particle size range of the small solid electrolyte particles is 0.01umˉ15um, and the particle size range of the large solid electrolyte particles is 15umˉ500um, um is micrometer. The positive electrode material can be a positive electrode ternary NCM, lithium iron phosphate LFP, lithium manganese-rich LMR, lithium cobalt oxide LCO or lithium manganese iron phosphate LMFP, etc. The solid electrolyte can be: sulfide electrolyte: lithium phosphorus sulfur LPS, lithium phosphorus sulfur chlorine LPSCl, lithium germanium phosphorus sulfur LGPS, etc.; oxide solid electrolyte: lithium aluminum titanium phosphate LATP, lithium lanthanum zirconium oxide LLZO, lithium lanthanum titanium oxide LLTO, etc.; polymer solid electrolyte: polyethylene oxide PEO, polyvinyl carbonate PVC, polydioxolane PDOL, polysiloxane PS, polyethylene glycol PEG, etc. The conductive agent mentioned above can be carbon black SP, Ketjen black ECP, carbon nanotube CNT, graphene or vapor-grown carbon fiber reinforcement VGCF. The binder mentioned above can be polytetrafluoroethylene PTFE, polyvinylidene fluoride PVDF, P-type polyaniline PAN, polymethyl methacrylate PMMA or hydrogenated nitrile rubber HNBR, etc.
[0059] In one embodiment, the step of configuring the positive electrode small particles, the solid electrolyte small particles, the conductive agent, the binder and the dry ice particles into a low-temperature dry slurry comprises:
[0060] The positive electrode small particles, solid electrolyte small particles, conductive agent and binder are prepared into a low-temperature dry slurry in a mass ratio of 60ˉ85:14ˉ30:0.5ˉ5:0.5ˉ5, and dry ice accounts for 0.5% to 5% of the total mass of the four substances in the first layer, namely, the positive electrode small particles, solid electrolyte small particles, conductive agent and binder.
[0061] In the embodiment of the present application, the mass ratio of the positive electrode small particles, solid electrolyte small particles, conductive agent, and binder is 60-85:14-30:0.5-5:0.5-5; dry ice accounts for 0.5% to 5% of the total mass of the four substances of positive electrode small particles, solid electrolyte small particles, conductive agent, and binder in the first layer. The embodiment of the present invention ensures that the first layer can provide fast lithium ion and electron transmission and reduce ohmic impedance and lithium ion transfer impedance by making each component in the first layer of slurry within a reasonable range. At the same time, the gasification of dry ice increases the porosity and reduces the tortuosity.
[0062] In one embodiment, the step of configuring the cathode large particles, the solid electrolyte small particles, the conductive agent, the binder and the dry ice particles into a low-temperature dry slurry comprises:
[0063] The positive electrode huge particles, solid electrolyte small particles, conductive agent, and binder are prepared into a low-temperature dry slurry in a mass ratio of 70-97:2-20:0.5-5:0.5-5, and dry ice accounts for 0.5%-5% of the total mass of the four substances in the second layer, namely, the positive electrode huge particles, solid electrolyte small particles, conductive agent, and binder.
[0064] In the embodiment of the present application, the mass ratio of the positive electrode particles, the solid electrolyte particles, the conductive agent, and the binder is 70-97:2-20:0.5-5:0.5-5; dry ice accounts for 0.5% to 5% of the total mass of the four substances of the positive electrode particles, the solid electrolyte particles, the conductive agent, and the binder in the second layer. The embodiment of the present invention ensures that the second layer 3 can provide fast lithium ion transport and high load and high pressure by making each component in the second layer slurry within a reasonable range, thereby improving the surface density and energy density of the pole piece. At the same time, the gasification of dry ice increases the porosity and reduces the tortuosity.
[0065] In one embodiment, the step of configuring the positive electrode small particles, the solid electrolyte large particles, the conductive agent, the binder and the dry ice particles into a low-temperature dry slurry comprises:
[0066] The small positive electrode particles, large solid electrolyte particles, conductive agent, and binder are configured into a low-temperature dry slurry in a mass ratio of 45-79:20-45:0.5-5:0.5-5, and dry ice accounts for 0.5% to 5% of the total mass of the four substances in the third layer, namely, the small positive electrode particles, large solid electrolyte particles, conductive agent, and binder.
[0067] In the embodiment of the present application, the mass ratio of the positive electrode small particles, solid electrolyte large particles, conductive agent, and binder is 45-79:20-45:0.5-5:0.5-5; dry ice accounts for 0.5% to 5% of the total mass of the four substances of positive electrode small particles, solid electrolyte large particles, conductive agent, and binder in the third layer. The embodiment of the present invention ensures that the third layer 4 provides fast lithium ion transmission and electronic insulation by making each component in the third layer slurry within a reasonable range, avoiding the occurrence of interface side reactions, improving interface stability, and improving circulation; at the same time, the gasification of dry ice increases porosity and reduces tortuosity.
[0068] In one embodiment, the step of configuring the solid electrolyte small particles, the conductive agent and the binder into a slurry comprises:
[0069] The solid electrolyte small particles, the conductive agent and the binder are prepared into a slurry in a mass ratio of 90-99:0.5-5:0.5-5.
[0070] In the embodiment of the present application, in the slurry applied to the perforation, the mass ratio of the solid electrolyte small particles, the conductive agent, and the binder is 90-99: 0.5-5: 0.5-5. The embodiment of the present invention further ensures the construction of a channel for rapid lithium ion transmission, reduces lithium ion transfer impedance, and improves rate performance by making the components of the slurry applied to the perforation within a reasonable range.
[0071] In one embodiment, the diameter of the hole formed by punching is 1 mm to 10 mm.
[0072] In the embodiment of the present application, if the hole formed at the punching point is too small, the solid electrolyte slurry is not easy to infiltrate; if the hole is too large, the proportion of inactive ingredients, such as solid electrolyte, will be too large, affecting the proportion of active substances. By designing the hole diameter range to be 1 mm to 10 mm, a channel for rapid transmission of lithium ions can be better constructed, reducing the lithium ion transfer impedance and improving the rate performance.
[0073] In one embodiment, the diameter of the pores formed by the dry ice particles being vaporized under hot pressure is 0.1 micrometers to 10 micrometers.
[0074] In the embodiment of the present application, the pores formed by the hot-pressed vaporization of dry ice particles are micron-sized pores, that is, the diameter of the pores is micron-sized, and the solid electrolyte is filled in the millimeter-sized pores and micron-sized pores formed by drilling to better construct a highway for ion transmission and reduce the lithium ion transmission impedance.
[0075] The present application also provides a method for preparing a solid-state secondary battery, the method comprising:
[0076] A solid-state secondary battery positive electrode sheet is prepared by using the solid-state secondary battery positive electrode preparation method described in any of the above embodiments;
[0077] A solid-state secondary battery negative electrode sheet is prepared; specifically, silicon carbon, a conductive agent, a binder, and a solid electrolyte are made into a negative electrode sheet; more specifically, the negative electrode sheet is made according to a mass ratio of silicon carbon: conductive agent: binder: solid electrolyte = 50-95: 0.5-10: 0.5-5: 4-35.
[0078] Prepare a solid electrolyte sheet; specifically, prepare a sulfide electrolyte and a binder into a solid electrolyte sheet; more specifically, prepare the solid electrolyte sheet according to a mass ratio of sulfide electrolyte: binder = 90-99.5:0.5-10;
[0079] A solid-state secondary battery positive electrode sheet, a solid-state secondary battery negative electrode sheet, and a solid-state electrolyte sheet are combined to form a solid-state battery.
[0080] After a solid-state battery is assembled, it can be cycled and tested to verify its performance.
[0081] Comparative Example
[0082] (1) The positive electrode NCM, solid electrolyte LPSCl, conductive agent SP, and binder PTFE are prepared into a dry slurry in a mass ratio of 75:22:1:2, coated on an aluminum foil and hot pressed into a film to form a positive electrode sheet.
[0083] (2) Negative electrode silicon carbon, conductive agent SP, binder PTFE 、 The solid electrolyte LPSCl was prepared into a negative electrode sheet according to a mass ratio of 83:5:2:10;
[0084] (3) solid electrolyte LPSCl and binder PTFE are prepared into a solid electrolyte sheet in a mass ratio of 99:1;
[0085] (4) Assemble the above-mentioned positive electrode sheet, solid electrolyte sheet, and negative electrode sheet into a battery for cycle testing.
[0086] Example 1
[0087] (1) The positive electrode NCM small particles, the solid electrolyte LPSCl small particles, the conductive agent SP, the binder PTFE are configured into a low-temperature dry process slurry in a mass ratio of 75:22:1:2, and a total amount of 1% dry ice, which is coated on an aluminum foil and hot pressed into a film to form a first layer; wherein the total amount of 1% dry ice mentioned in this paragraph means that the dry ice accounts for 1% of the total mass of the four substances of the positive electrode NCM small particles, the solid electrolyte LPSCl small particles, the conductive agent SP, and the binder PTFE in the first layer;
[0088] (2) The large positive electrode NCM particles, the small solid electrolyte LPSCl particles, the conductive agent SP, the binder PTFE are prepared into a low-temperature dry process slurry in a mass ratio of 92:5:1:2, and a total amount of 1% dry ice, which is coated on an aluminum foil and hot pressed into a film to form a second layer; wherein the total amount of 1% dry ice mentioned in this paragraph means that the dry ice accounts for 1% of the total mass of the four substances of the large positive electrode NCM particles, the small solid electrolyte LPSCl particles, the conductive agent SP, and the binder PTFE in the second layer;
[0089] (3) The positive electrode NCM small particles, the solid electrolyte LPSCl large particles, the conductive agent SP, the binder PTFE are configured into a low-temperature dry process slurry according to a mass ratio of 60:37:1:2, and a total amount of 1% dry ice, which is coated on an aluminum foil and hot pressed into a film to form a third layer; wherein the total amount of 1% dry ice mentioned in this paragraph means that the dry ice accounts for 1% of the total mass of the four substances of the positive electrode NCM small particles, the solid electrolyte LPSCl large particles, the conductive agent SP, and the binder PTFE in the third layer;
[0090] (4) Using laser to clean and punch holes in the positive electrode sheet until the foil is formed, the holes have a diameter of 1 mm and are arranged in a lateral pattern;
[0091] (5) Small particles of solid electrolyte LPSCl, conductive agent SP, and binder PTFE are coated on the laser-cleaned and punched areas in a mass ratio of 97:1:2, and then dried to form a positive electrode sheet; wherein the solid electrolyte is filled in the micrometer-scale holes left by the vaporization of dry ice and the millimeter-scale holes left by the laser punching;
[0092] (6) preparing a negative electrode sheet with a mass ratio of 83:5:2:10 of negative electrode silicon carbon, conductive agent SP, binder PTFE, and solid electrolyte LPSCl;
[0093] (7) preparing a solid electrolyte sheet with a mass ratio of LPSC1 and a binder PTFE of 99:1;
[0094] (8) Assemble the positive electrode sheet, solid electrolyte sheet, and negative electrode sheet into a battery for cycle testing.
[0095] Example 2
[0096] (1) The positive electrode NCM small particles, the solid electrolyte LPSCl small particles, the conductive agent SP, the binder PTFE are configured into a low-temperature dry process slurry in a mass ratio of 75:22:1:2, and a total amount of 1% dry ice, which is coated on an aluminum foil and hot pressed into a film to form a first layer; wherein the total amount of 1% dry ice mentioned in this paragraph means that the dry ice accounts for 1% of the total mass of the four substances of the positive electrode NCM small particles, the solid electrolyte LPSCl small particles, the conductive agent SP, and the binder PTFE in the first layer;
[0097] (2) The large positive electrode NCM particles, the small solid electrolyte LPSCl particles, the conductive agent SP, the binder PTFE are prepared into a low-temperature dry process slurry in a mass ratio of 92:5:1:2, and a total amount of 1% dry ice, which is coated on an aluminum foil and hot pressed into a film to form a second layer; wherein the total amount of 1% dry ice mentioned in this paragraph means that the dry ice accounts for 1% of the total mass of the four substances of the large positive electrode NCM particles, the small solid electrolyte LPSCl particles, the conductive agent SP, and the binder PTFE in the second layer;
[0098] (3) The positive electrode NCM small particles, the solid electrolyte LPSCl large particles, the conductive agent SP, the binder PTFE are configured into a low-temperature dry process slurry according to a mass ratio of 60:37:1:2, and a total amount of 1% dry ice, which is coated on an aluminum foil and hot pressed into a film to form a third layer; wherein the total amount of 1% dry ice mentioned in this paragraph means that the dry ice accounts for 1% of the total mass of the four substances of the positive electrode NCM small particles, the solid electrolyte LPSCl large particles, the conductive agent SP, and the binder PTFE in the third layer;
[0099] (4) Using laser to clean the positive electrode sheet until the foil is formed, forming holes with a diameter of 5 mm, arranged in a lateral pattern;
[0100] (5) Small particles of solid electrolyte LPSCl, conductive agent SP, and binder PTFE are coated on the punched holes in a mass ratio of 97:1:2 and dried. The solid electrolyte is filled in the micrometer-scale holes left by dry ice vaporization and the millimeter-scale holes left by laser drilling;
[0101] (6) preparing a negative electrode sheet with a mass ratio of 83:5:2:10 of negative electrode silicon carbon, conductive agent SP, binder PTFE, and solid electrolyte LPSCl;
[0102] (7) preparing a solid electrolyte sheet with a mass ratio of LPSC1 and a binder PTFE of 99:1;
[0103] (8) Assemble the positive electrode sheet, solid electrolyte sheet, and negative electrode sheet into a battery for cycle testing.
[0104] Example 3
[0105] (1) The positive electrode NCM small particles, the solid electrolyte LPSCl small particles, the conductive agent SP, the binder PTFE are configured into a low-temperature dry process slurry in a mass ratio of 75:22:1:2, and a total amount of 1% dry ice, which is coated on an aluminum foil and hot pressed into a film to form a first layer; wherein the total amount of 1% dry ice mentioned in this paragraph means that the dry ice accounts for 1% of the total mass of the four substances of the positive electrode NCM small particles, the solid electrolyte LPSCl small particles, the conductive agent SP, and the binder PTFE in the first layer;
[0106] (2) The large positive electrode NCM particles, the small solid electrolyte LPSCl particles, the conductive agent, the binder are configured into a low-temperature dry process slurry in a mass ratio of 92:5:1:2, and the total amount of dry ice is 1%, which is coated on an aluminum foil and hot pressed into a film to form a second layer; wherein the total amount of dry ice of 1% mentioned in this paragraph means that the dry ice accounts for 1% of the total mass of the four substances of the large positive electrode NCM particles, the small solid electrolyte LPSCl particles, the conductive agent SP, and the binder PTFE in the second layer;
[0107] (3) The positive electrode NCM small particles, the solid electrolyte LPSCl large particles, the conductive agent SP, the binder PTFE are configured into a low-temperature dry process slurry according to a mass ratio of 60:37:1:2, and a total amount of 1% dry ice, which is coated on an aluminum foil and hot pressed into a film to form a third layer; wherein the total amount of 1% dry ice mentioned in this paragraph means that the dry ice accounts for 1% of the total mass of the four substances of the positive electrode NCM small particles, the solid electrolyte LPSCl large particles, the conductive agent SP, and the binder PTFE in the third layer;
[0108] (4) Using laser to clean and punch holes in the positive electrode sheet until the foil is formed, the holes have a diameter of 10 mm and are arranged in a lateral pattern;
[0109] (5) solid electrolyte small particles LPSCl, conductive agent SP, and binder PTFE are coated on the punched holes in a mass ratio of 97:1:2, and dried to form a positive electrode sheet; wherein the solid electrolyte is filled in the micrometer-scale holes left by the vaporization of dry ice and the millimeter-scale holes left by the laser drilling;
[0110] (6) preparing a negative electrode sheet with a mass ratio of 83:5:2:10 among negative electrode silicon carbon, conductive agent SP, binder PTFE, and solid electrolyte LPSCl;
[0111] (7) solid electrolyte LPSCl and binder PTFE are prepared into a solid electrolyte sheet in a mass ratio of 99:1;
[0112] (8) Assemble the positive electrode sheet, solid electrolyte sheet, and negative electrode sheet into a battery for cycle testing.
[0113] Table 1 Cycle performance
[0114]
[0115] In the above embodiments 1-3, the proportion of the positive electrode NCM in the second layer is higher than that in the comparative example. Therefore, the energy density of the second layer in the above embodiments 1-3 is higher than that in the comparative example. The energy density of all solid-state secondary batteries in the above embodiments 1-3 is higher than that in the comparative example.
[0116] The comparative examples in the following Table 2 follow the above comparative examples. Except for the different proportions of the components injected in the first layer, the second layer, the third layer and the punching place, Examples 4 and 5 are the same as Example 2.
[0117] Table 2 Cycle performance
[0118]
[0119] As can be seen from Table 1-2, the present application can reduce DCR (DC internal resistance) and improve rate performance and cycle performance relative to the comparative example.
[0120] The comparative examples in the following Table 3 follow the above comparative examples. Except for the different proportions of the components in the first layer, the other aspects of Examples 6 and 7 are the same as those of Example 2.
[0121] Table 3
[0122]
[0123]
[0124] It can be seen from Table 3 that the first layer of the positive electrode of the solid-state secondary battery of the present application provides fast lithium ion and electron transmission, and reduces ohmic impedance and lithium ion transfer impedance.
[0125] The comparative examples in the following Table 4 follow the above comparative examples. Except for the different proportions of the components in the second layer, Examples 8 and 9 are the same as Example 2.
[0126] Table 4
[0127] The composition and proportion of the second layer 1C / 0.33C capacity retention rate Comparative Example / 85% Example 2 92:5:1:2 97.8% Example 8 70:20:5:5 97.5% Example 9 97:2:0.5:0.5 95.5%
[0128] It can be seen from Table 4 that the second layer of the positive electrode of the solid-state secondary battery of the present application provides fast lithium ion transport and high load and high pressure, thereby improving the electrode surface density and energy density.
[0129] The comparative examples in the following Table 5 follow the above comparative examples. Except for the different proportions of the components in the third layer, the other components of Examples 10 and 11 are the same as those of Example 2.
[0130] Table 5
[0131] The composition ratio of the third layer 200 cycle performance Comparative Example / 71% Example 2 60:37:1:2 94% Example 10 45:45:5:5 96% Embodiment 11 79:20:0.5:0.5 92%
[0132] It can be seen from Table 5 that the third layer of the positive electrode of the solid-state secondary battery of the present application provides fast lithium ion transmission and electronic insulation, avoids the occurrence of interface side reactions, improves interface stability, and enhances the cycle.
[0133] The comparative examples in the following Table 6 follow the above comparative examples. Except for the different proportions of the components injected at the punching point, Examples 12 and 13 are the same as Example 2.
[0134] Table 6
[0135]
[0136]
[0137] It can be seen from Table 6 that the slurry applied to the perforated area helps to build a channel for rapid lithium ion transmission, reduce lithium ion transfer impedance, and improve rate performance.
[0138] In summary, the present application configures the positive electrode small particles, solid electrolyte small particles, conductive agent, binder and dry ice particles into a low-temperature dry slurry in a certain proportion, applies it on any surface of the positive electrode collector 1 and performs hot pressing to form a film to form a first layer, and the first layer provides fast lithium ion and electron transmission, reduces ohmic impedance and lithium ion transfer impedance; configures the positive electrode large particles, solid electrolyte small particles, conductive agent, binder and dry ice particles into a low-temperature dry slurry in a certain proportion, applies it on the first layer and performs hot pressing to form a film to form a second layer; the second layer provides fast lithium ion transport and high load and high pressure, and improves the electrode surface density and energy density; configures the positive electrode small particles, solid electrolyte large particles, conductive agent, binder and dry ice particles into a low-temperature dry slurry in a certain proportion, applies it on the second layer and performs hot pressing to form a film to form a third layer, and the third layer provides fast lithium ion transmission and electronic insulation, avoids the occurrence of interface side reactions, improves interface stability, and enhances circulation. In addition, during the hot pressing process to form a film, the dry ice vaporizes and leaves the electrode, leaving holes at the original position, thereby increasing the porosity and reducing the tortuosity; the electrode is punched to build a highway for ion transmission, reducing the lithium ion transmission impedance and improving the rate performance and cycle performance.
[0139] It should be noted that, in this article, the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, device, article or method including a series of elements includes not only those elements, but also includes other elements not explicitly listed, or also includes elements inherent to such process, device, article or method. In the absence of further restrictions, an element defined by the sentence "includes a ..." does not exclude the presence of other identical elements in the process, device, article or method including the element.
[0140] The above description is only a preferred embodiment of the present application, and does not limit the patent scope of the present application. Any equivalent structure or equivalent process transformation made using the contents of the present application specification and drawings, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present application.
Claims
1. A solid-state secondary battery positive electrode, characterized in that: include: Positive electrode current collector; A first layer located on the positive electrode current collector; the first layer comprises small positive electrode particles, small solid electrolyte particles, a conductive agent and a binder; A second layer located on the first layer; the second layer further comprises positive electrode particles, solid electrolyte particles, a conductive agent and a binder; a third layer located on the second layer; the third layer comprises small positive electrode particles, large solid electrolyte particles, a conductive agent and a binder; wherein the particle size of the small positive electrode particles is smaller than the particle size of the large positive electrode particles, and the particle size of the small solid electrolyte particles is smaller than the particle size of the large solid electrolyte particles; Micrometer-sized pores distributed in the first layer, the second layer and the third layer; the micrometer-sized pores are filled with small solid electrolyte particles, a conductive agent and a binder; Millimeter-scale holes penetrate the first layer, the second layer and the third layer, and are filled with small solid electrolyte particles, a conductive agent and a binder.
2. A method for preparing a positive electrode of a solid-state secondary battery, characterized in that: The method is used to prepare the solid-state secondary battery positive electrode according to claim 1, and the method comprises: The positive electrode small particles, solid electrolyte small particles, conductive agent, binder and dry ice particles are configured into a low-temperature dry slurry, which is coated on the positive electrode current collector and hot pressed into a film to form a first layer; The cathode large particles, solid electrolyte small particles, conductive agent, binder and dry ice particles are configured into a low-temperature dry slurry, which is coated on the first layer and hot pressed into a film to form a second layer; The small positive electrode particles, the large solid electrolyte particles, the conductive agent, the binder and the dry ice particles are configured into a low-temperature dry slurry, which is coated on the second layer and hot pressed into a film to form a third layer; The formed three-layer electrode is then punched; Small solid electrolyte particles, a conductive agent and a binder are prepared into a slurry, applied to the punched areas, and dried.
3. The method for preparing a positive electrode of a solid-state secondary battery according to claim 2, characterized in that: The step of configuring the positive electrode small particles, solid electrolyte small particles, conductive agent, binder and dry ice particles into low-temperature dry slurry comprises: The positive electrode small particles, solid electrolyte small particles, conductive agent, and binder are configured into a low-temperature dry slurry in a mass ratio of 60-85:14-30:0.5-5:0.5-5, and dry ice accounts for 0.5% to 5% of the total mass of the four substances of the positive electrode small particles, solid electrolyte small particles, conductive agent and binder in the first layer.
4. The method for preparing a positive electrode of a solid-state secondary battery according to claim 2, characterized in that: The step of configuring the positive electrode large particles, the solid electrolyte small particles, the conductive agent, the binder and the dry ice particles into a low-temperature dry slurry comprises: The positive electrode huge particles, solid electrolyte small particles, conductive agent, and binder are prepared into a low-temperature dry slurry in a mass ratio of 70-97:2-20:0.5-5:0.5-5, and dry ice accounts for 0.5%-5% of the total mass of the four substances in the second layer, namely, the positive electrode huge particles, solid electrolyte small particles, conductive agent, and binder.
5. The method for preparing a positive electrode of a solid-state secondary battery according to claim 2, characterized in that: The step of configuring the positive electrode small particles, the solid electrolyte large particles, the conductive agent, the binder and the dry ice particles into a low-temperature dry slurry comprises: The small positive electrode particles, large solid electrolyte particles, conductive agent, and binder are configured into a low-temperature dry slurry in a mass ratio of 45-79:20-45:0.5-5:0.5-5, and dry ice accounts for 0.5% to 5% of the total mass of the four substances in the third layer, namely, the small positive electrode particles, large solid electrolyte particles, conductive agent, and binder.
6. The method for preparing a positive electrode of a solid-state secondary battery according to claim 2, characterized in that: The step of configuring the solid electrolyte small particles, the conductive agent and the binder into a slurry comprises: The solid electrolyte small particles, the conductive agent and the binder are prepared into a slurry in a mass ratio of 90-99:0.5-5:0.5-5.
7. The method for preparing a positive electrode of a solid-state secondary battery according to claim 2, characterized in that: The diameter of the hole formed by the punching is 1 mm to 10 mm.
8. The method for preparing a positive electrode of a solid-state secondary battery according to claim 2, characterized in that: The diameter of the pores formed by the dry ice particles being vaporized under hot pressure is 0.1 micrometer to 10 micrometers.
9. A solid-state secondary battery, characterized in that: The solid-state secondary battery comprises the solid-state secondary battery positive electrode according to claim 1.
Citation Information
Cited By
Solid-state secondary battery positive electrode, preparation method for solid-state secondary battery positive electrode, and solid-state secondary battery
WO2026091608A1